Exploring gender differences in the vulnerability towards drug abuse among adolescents in Malaysia - Wan Shahrazad Wan Sulaiman; Mohammad Rahim Kamaluddin; Ezarina Zakaria; Fauziah Ibrahim; Nazirah Hassan; Jamiah Manap; Salina Nen; Zainah Ahmad Zamani; Fatimah Yusooff (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Protective and risk factors are important in reducing vulnerability towards drug abuse among adolescents. This study, therefore, aims to explore gender differences in such vulnerability in high-risk areas identified by the National Anti-Drugs Agency Malaysia. The study employs a survey design, with questionnaires distributed to 213 adolescents who fulfilled the inclusion criteria. The researchers developed the questionnaire and comprised five parts: the demographic profile, interpersonal conflict, negative emotions, social support, and mental health. The data were analyzed using descriptive and inferential statistics. The results show no significant gender differences in interpersonal conflict, negative emotions, and mental health. However, there was a significant difference in social support based on gender, with females showing a higher mean than males. These findings imply the importance of identifying the relevant factors to prevent early involvement in drug abuse.